Hydrogen sulfide and nitric oxide signal integration and plant development under stressed/non-stressed condition : editorial - Singh, Vijay Pratap; Tripathi, Durgesh Kumar; Fotopoulos, Vasileios (My University, 2020)
In the past decade, hydrogen sulfide (H2S) and nitricoxide (NO) have emerged as major signaling moleculeswhich are involved in most life cycle processes in plants,i.e. from seed germination to plant death. H2S and NO-regulated development of plants requires integration ofcomplex signaling networks and also involves other sig-naling pathways. Moreover, to re-establish cellular redoxhomeostasis under stress conditions, regulation of geneexpression takes place, which helps in achieving anappropriate plant response. In this context, the most sig-nificant controls occur at the transcriptional, post-transcriptional and post-translational levels which helpin acquiring adaptive changes in stress-challengedplants. Although various studies have demonstrated therole of H2S and NO in regulating a plethora of plantgrowth and development processes under stressed/non-stressed conditions, much remains to be elucidatedregarding their roles in plant biology. Therefore, this spe-cial issue was organized to collect state-of-the-art plantresearch involving H2S and NO under changing environ-mental conditions. This special issue has collected sevenreviews and 11 original research articles aimed at com-piling a comprehensive status quo on the implication ofH2S and NO signaling in plant biology.
Keywords: hydrogen sulfide (H2S); nitricoxide (NO)